Increased risk for other cancers in individuals with Ewing sarcoma and their relatives - Diana Abbott; Schuyler O'Brien; James M. Farnham; Erin L. Young; Jeffrey Yap; Kevin Jones; Stephen L. Lessnick; R. Lor Randall; Joshua D. Schiffman; Lisa A. Cannon‐Albright (Cancer Medicine, 2019)
Abstract Background There are few reports of the association of other cancers with Ewing sarcoma in patients and their relatives. We use a resource combining statewide genealogy and cancer reporting to provide unbiased risks. Methods Using a combined genealogy of 2.3 million Utah individuals and the Utah Cancer Registry (UCR), relative risks (RRs) for cancers of other sites were estimated in 143 Ewing sarcoma patients using a Cox proportional hazards model with matched controls; however, risks in relatives were estimated using internal cohort‐specific cancer rates in first‐, second‐, and third‐degree relatives. Results Cancers of three sites (breast, brain, complex genotype/karyotype sarcoma) were observed in excess in Ewing sarcoma patients. No Ewing sarcoma patients were identified among first‐, second‐, or third‐degree relatives of Ewing sarcoma patients. Significantly increased risk for brain, lung/bronchus, female genital, and prostate cancer was observed in first‐degree relatives. Significantly increased risks were observed in second‐degree relatives for breast cancer, nonmelanoma eye cancer, malignant peripheral nerve sheath cancer, non‐Hodgkin lymphoma, and translocation sarcomas. Significantly increased risks for stomach cancer, prostate cancer, and acute lymphocytic leukemia were observed in third‐degree relatives. Conclusions This analysis of risk for cancer among Ewing sarcoma patients and their relatives indicates evidence for some increased cancer predisposition in this population which can be used to individualize consideration of potential treatment of patients and screening of patients and relatives.